Tourists, travellers, refugees: An interview with Michelle De Kretser. Issue 5 (2nd September 2016) - Watkins, Alexandra
Abstract: Michelle De Kretser was born in Sri Lanka (then Ceylon) and moved to Australia in 1972. From 1989 to 1992 she was a founding editor of the Australian Women's Book Review . She is the author of several novels, including The Rose Grower (1999), The Hamilton Case (2003 – winner of the Tasmania Pacific Prize, the Encore Award [UK] and the Commonwealth Writers Prize [Southeast Asia and Pacific]) and The Lost Dog (2007). Her most recent novel, Questions of Travel, won the 2013 Miles Franklin Award, the Australian Literature Society Gold Medal and the 2013 Prime Minister's Literary Awards for fiction. In this conversation, which took place by telephone call from Melbourne to Sydney in August 2015, De Kretser discusses Questions of Travel in relation to travel and tourism, the Sri Lankan diaspora, and postcolonial and neocolonial politics.